Application Development and Content Validation of "SinoBed" for Pressure Ulcer Prevention and Monitoring - Taryudi, Taryudi; Lindayani, Linlin; Darmawati, Irma; Mutiar, Astri; Wijaya, Silman Silman Juwana (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: This study aimed to describe the application development and validation of the "SinoBed" application for pressure ulcer prevention and monitoring. Methods: The Delphi technique was used in this study to validate the researchers' content. Twelve specialists willing to help with this research validate the content of the SinoBed application. The experts were invited through email to participate in the study, and they were then issued an electronic form to fill out and return for evaluation. The data collecting tool was created using the Google Forms® platform and included a sociodemographic survey of the participants and an evaluative survey with seventeen closed-ended questions. We used the CVI (Content Validity Index) to check the information and modified kappa. Results: The study involved twenty experts, but only twelve participated. The I-CVI ranged from 0.92 to 1.00. The summary received mostly positive expert assessments throughout the study. The SinoBed app has a collection of five unique algorithms. The topics to be discussed in this paper include: 1) Identification creation, 2) Roles as a patient or nurse, 3) Monitoring position and mobilization, 4) Nursing care plan, and 5) Education. Conclusion: The content supplied in SinoBed® was validated using an expert consensus. The experts determined that the mobile application is suitable for preventing pressure ulcers.